Pemberian Pembebasan Bersyarat bagi Narapidana Narkotika pada Lapas Kelas I Madiun - Mochamad Fardhil Prismawan; Mitro Subroto (Law Department, Sharia and Law Faculty., 2022)
There are provisions concerning criminal sanctions in the implementation of criminal law. where there is a purpose of imposing criminal sanctions for convicted offenders. The purpose of the imposition of criminal sanctions should not be solely to encourage the existence of a retaliation. In this case the Correctional institution is one of the executors of the purpose of the penal system in the improvement system As stated in the legislation, a number of law enforcement efforts to ensure that inmates are punished to be aware of their mistakes, in order to correct themselves and will not repeat crimes as well as then they are acceptable to be returned by the community, actively participate in the development and live a fair living as a good citizen and responsible criminal law, accordingly on law regulations act No. 12 Of 1995 about correctional regulations to regulate all rights of inmates. In the first letter k section 14 of the Act (Act No. 12 of 1995) it says